The Influence of Leadership Style, Compensation and Work Environment on Employee Performance with Motivation as an Intervening Variable: Pengaruh Gaya Kepemimpinan, Kompensasi dan Lingkungan Kerja terhadap Kinerja Karyawan dengan Motivasi sebagai Variabel Intervening - Mayasari, Eva; Harjatno, Slamet (Indonesian Journal of Law and Economics Review, 2023)
This study aims to determine the effect of leadership style, compensation and work environment on employee performance throught motivation as an intervening variable at UD. Jaya Usaha Snack. The method in this study using quantitative. Data collection was carried out using interview and questionnaires that had been distributed to all employess, totaling 50 employees who were used as research responden. The results of data processing using IBM SPSS using path analysis techniques.